Charter and Revised Ordinances of Boise City, Idaho 111 (1894) - (:unkn) unknown (My University, 1894)
§ 9: Prohibited the carry, use for amusement, or have in possession any air gun or spring gun. Violators fined not exceeding ten dollars, or be imprisoned in the city jail not more than five days, or both fine and imprisonment.
Keywords: CARRY